Analysis Of Waqf Fundraising Strategies At Masjid Al-Hidayah BCV: An Analytical Hierarchy Process Approach Study - Yasir, Sulaeman; Ayuniyyah, Qurroh; Supriyanto, Trisiladi (Fakultas Agama Islam, Universitas Ibn Khaldun Bogor, 2024)
In practice, waqf (Islamic endowment) in Indonesia faces many difficult challenges, as it is generally known as unproductive waqf. Cash waqf has the potential to not only serve as a religious ritual but also to empower public welfare. This study aims to identify the priority factors that hinder the development of cash waqf practices at Al-Hidayah BCV Mosque using the Analytic Hierarchy Process (AHP) method, as well as to offer solutions for the identified issues. The research findings indicate that the problems in managing cash waqf at Al-Hidayah BCV Mosque are divided into four key aspects: Human, Trust, System, and Economic. The ranking of issues from highest to lowest priority is: 1) Human (with the highest priority sub-criterion: Human Resources); 2) Trust (with the highest priority sub-criterion: Commitment); 3) System (with the highest priority sub-criterion: Innovation); 4) Economic (with the highest priority sub-criterion: Funding). The solutions to these issues, based on priority, are: 1) Human (with the highest priority sub-criterion: Leadership); 2) Trust (with the highest priority sub-criterion: Transparency); 3) System (with the highest priority sub-criterion: Legal Entity); 4) Economic (with the highest priority sub-criterion: Collaboration). The strategies for these issues, based on priority, are: 1) Partnership (with the highest priority sub-criterion); 2) Strong Message (with the second highest priority sub-criterion); 3) Program Variation (with the third highest priority sub-criterion); 4) Reward (with the lowest priority sub-criterion).